EULER CHARACTERISTIC OF TANGO BUNDLES - Hong Cong Nguyen; Tuan Hiep Dang; Thi Mai Van Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
We are interested in a vector bundle constructed by Tango (1976). The Tango bundle is an indecomposable vector bundle of rank \(n-1\) on the complex projective space \(\mathbb{P}^n\). In particular, we show that the Euler characteristic of the Tango bundle on \(\mathbb{P}^n\) is equal to \(2n-1\).